2011
DOI: 10.1007/s00187-011-0128-5
|View full text |Cite
|
Sign up to set email alerts
|

The routinisation of management controls in software

Abstract: Our paper aims to explore management control as complex and intertwining process over time, rather than the (mainstream) fixation on rational, optimising tools for ensuring business success. We set out to contribute towards our understanding of why and how particular management controls evolve over time as they do. We discuss how the management control routines of one organisation emerged and reproduced (through software), and moved towards a situation of becoming accepted and generally unquestioned across muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
(17 reference statements)
0
10
0
2
Order By: Relevance
“…Ribeiro and Scapens (2006) concluded that powerful individuals (and power more generally) can play an important role in facilitating or resisting accounting change. So, whereas Burns and Scapens (2000) recognised that resistance can be due to following taken-for-granted assumptions (which others have called the power of the system -see Hardy, 1996 andBurns, 2000), later studies have highlighted how the more explicit exercise of power can either facilitate change or create resistance to it (see also Burns and Nielsen, 2006;Burns and Quinn, 2011;and Van der Steen, 2011).…”
Section: Studies Using the Bands Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribeiro and Scapens (2006) concluded that powerful individuals (and power more generally) can play an important role in facilitating or resisting accounting change. So, whereas Burns and Scapens (2000) recognised that resistance can be due to following taken-for-granted assumptions (which others have called the power of the system -see Hardy, 1996 andBurns, 2000), later studies have highlighted how the more explicit exercise of power can either facilitate change or create resistance to it (see also Burns and Nielsen, 2006;Burns and Quinn, 2011;and Van der Steen, 2011).…”
Section: Studies Using the Bands Frameworkmentioning
confidence: 99%
“…However, it has attracted some criticism and researchers who have used it to study management accounting practices have identified a number of issues which deserve greater attention. For instance, Dillard et al (2004) criticised the B&S framework for its failure to explicitly recognise the impact of broader (field level) institutions, while others have pointed to issues of agency, power and the role of trust (see, for example, Burns, 2000;Johansson and Baldvinsdottir, 2003;Burns and Nielsen, 2006;Busco et al, 2006;Yazdifar et al, 2008;Burns and Quinn, 2011;and Van der Steen, 2011). In extending the B&S framework we address these criticisms and incorporate the issues which have been identified as deserving greater attention.…”
Section: Introductionmentioning
confidence: 99%
“…Scapens (2006) afirma que a rotinização e a institucionalização estão no cerne da estrutura de Burns e Scapens (2000). A estrutura de Burns e Scapens (2000) foi amplamente adotada para explicar a mudança da contabilidade gerencial, em particular o processo de institucionalização de novas práticas (por exemplo, Burns & Quinn, 2011;Guerreiro, Pereira & Frezatti, 2006;Herbert & Seal, 2012 ;Lukka, 2007;Nor-Aziah & Scapens, 2007;Soin, Seal & Cullen, 2002;Yazdifar et al, 2008;Callado & Pinho,20142015Espejo & Eggert, 2017).…”
Section: O Processo De Institucionalizaçãounclassified
“…Powstaje zatem pytanie, jaka jest rola controllerów we współczesnych przedsiębiorstwach, skoro nie pośredniczą oni w przygotowywaniu raportów, gdyż system w bardzo prosty sposób wyręcza ich z tego obowiązku. Problem ten, choć obecny w opracowaniach naukowych, nie jest otwarcie dyskutowany w kręgach samych zainteresowanych [Burns, Quinn 2011;Weber, Strauss, Spittler 2012;Quinn, Kristandl 2013]. Belfo i Trigo [2013] zwrócili uwagę na nowy termin "accounting intelligence", który się ostatnio pojawił.…”
Section: Zakończenieunclassified